Keragaman Jenis Rayap pada Tiga Tegakan di Hutan Pendidikan Wanagama - PERDANA, Ade Darian ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Termites are cellulose-eating soil fauna which is important in the tropics. This insect which lives in colonies has diversity and high population abundance. It plays an important role in decomposition, nutrient turnover and processes in the soil. In Wanagama forest, there are several stands with different environmental characteristics that affect the diversity of subterranean termites species. The aim of the study was to know the diversity and abundance of subterranean termites in the stand of Tectona grandis, Acacia mangium, Eucalyptus sp. The study was conducted in July 2013 (dry season), in plot 17 Wanagama. Subterranean termites sampling was done with a combination of transect surveys methods and plot methods. As much as 2 transects were made in each stand, with 6 plots on each transect. The measurement of environmental factors consisted of soil moisture content, moisture content of litter, litter thickness, light intensity, temperature, pH ( H2O ) of land, basal area, and ground cover diversity . The study found 5 species of subterranean termites (Hypotermes sp. A., Odontotermes longignathus, Macrotermes gilvus, Microtermes insperatus, Pericapritermes semarangi) from 2 subfamilies (Macrotermitinae dan Termitinae). Those 2 subfamilies were from 1 family (Termitidae). The more litter thickness and dead wood existence caused the abundance of subterranean termites in T. grandis stand (8.433 n/ha) was more than the one in Eucalyptus sp. stand (6.333 n/ha) and A. mangium stand (2.267 n/ha) for the existence of litter and dead wood can be a microhabitat that affects termites activity to nest and find its food. Meanwhile, the more varied plant diversity and the more amount of soil and litter moisture content could make the termites diversity in Eucalyptus sp. (1,275), more than the one in A. mangium stand (1,169) and T. grandis stand (1,031). A forest which had more varied plant and more water supply was the ideal habitat for termites life because it could keep moisture condition favored by termites.